Some notes on the early history of the Tembe, 1280 AD-1800 AD - Mandla Mathebula (Contree, 2017)
The Tembe tribe, which resides south of Maputo Bay, originates from the present day Zimbabwe and is also linked through archaeological evidence to the ancient state of Mapungubwe. It migrated to Mozambique and later occupied the land south of Maputo Bay, straddling between Mozambique and South Africa, from Mkhuze and Maputo.